Reconstructing unseen transmission events to infer dengue dynamics from viral sequences - Henrik Salje (Nature Portfolio, 2021)
Phylogeographic analyses can provide broad descriptions of the spread of pathogens between populations, but are limited by incomplete sampling. Here, the authors develop an inference framework that reconstructs sequential transmission events and use it to characterise dynamics of dengue in Thailand.